Hypermethylation of PPARG-encoding gene promoter mediates fine particulate matter-induced pulmonary fibrosis by regulating the HMGB1/NLRP3 axis - Siyu Yang; Yaochuan Sun; Yajun Luo; Yingyi Liu; Mengyu Jiang; Jiayou Li; Qibing Zhang; Jun Bai (Ecotoxicology and Environmental Safety, 2024)
The inflammatory response induced by fine particulate matter (PM2.5), a common class of air pollutants, is an important trigger for the development of pulmonary fibrosis. However, the specific mechanisms responsible for this phenomenon are yet to be fully understood. To investigate the mechanisms behind the onset and progression of lung fibrosis owing to PM2.5 exposure, both rats and human bronchial epithelial cells were subjected to varying concentrations of PM2.5. The involvement of the PPARG/HMGB1/NLRP3 signaling pathway in developing lung fibrosis caused by PM2.5 was validated through the utilization of a PPARG agonist (rosiglitazone), a PPARG inhibitor (GW9662), and an HMGB1 inhibitor (glycyrrhizin). These outcomes highlighted the downregulation of PPARG expression and activation of the HMGB1/NLRP3 signaling pathway triggered by PM2.5, thereby eliciting inflammatory responses and promoting pulmonary fibrosis. Additionally, PM2.5 exposure-induced DNA hypermethylation of PPARG-encoding gene promoter downregulated PPARG expression. Moreover, the DNA methyltransferase inhibitor 5-azacytidine mitigated the hypermethylation of the PPARG-encoding gene promoter triggered by PM2.5. In conclusion, the HMGB1/NLRP3 signaling pathway was activated in pulmonary fibrosis triggered by PM2.5 through the hypermethylation of the PPARG-encoding gene promoter.